The eco-evolutionary raison d’être of natural products as support for sustainable bioprospecting - Pereira, Renato Crespo; Ramos, Ygor Jessé; Moreira, Davyson de Lima (Frontiers in Ecology and Evolution, 2025)
Since time immemorial, a wide range of terrestrial, aquatic, and marine organisms have been used to treat illnesses and diseases, owing to the broad diversity of natural products they produce. Although widely recognized for their medicinal properties, natural products are fundamentally the result of adaptive chemistry - or phenotypic expression - of the organisms that produce them, shaped by evolutionary pressures from natural environmental enemies. This article examines natural products through ecological, evolutionary, and conservation lenses, highlighting how these perspectives add complexity to the already lengthy and costly process of bioprospecting. Due to their origin and evolutionary history, only a small fraction of the many screened natural products exhibits biological activity relevant to human health, as these compounds did not evolve to possess pharmacological properties. Our viewpoint emphasizes the true raison d’être of the vast diversity of natural products and argues that this perspective should be integrated into bioprospecting efforts. We propose focus on the ecological roles of natural products to offer a more rational, productive, and sustainable approach to drug discovery - one that aligns with biodiversity conservation and economic development.